Preventive Measures Against The Vectors Of Malaria In Akanda, Southwest Gabon: Knowledge, Attitudes, Practices, And Beliefs - Pamba, Richard; Sevidzem, Silas Lendzele; Koumba, Aubin Armel; Zinga-Koumba, Christophe Roland; Melodie Ovono, Audrey Prisca; Mintsa-Nguema, Rodrigue; Mavoungou, Jacques François; Mbouloungou, Alexis; M’Foubou Kassa, Felicien; Ondo Kutomy, Pyazzi Obame (European Scientific Journal, ESJ, 2021)
Background: Reliable data on the Knowledge, Attitudes, Beliefs, and Practices (KABP) of the indigenes of Akanda and its environs on the different approaches to fight against vectors of malaria is lacking. Objective: To evaluate the KABP of the indigenes of Akanda and its environs on the different techniques used to fight against vectors of malaria. Materials and Methods: A cross sectional survey using semi-structured questionnaires was conducted on heads of randomly selected households at Akanda from April to June 2019. Results: We interviewed 369 heads of households and the population had a high literacy rate. It was noticed that 94% of respondents knew that mosquitoes could transmit malaria. More than 80% believed that Insecticide-Treated bed Nets (ITNs) could protect them from malaria infection. There was no preference in ITNs usage with age cohorts and seasons of the year. The ITNs owned by respondents were mostly purchased from shops. Respondents underlined that their reluctance to sleep under ITNs was because of their inability to breath under such conditions. Also, apart from the use of ITNs for malaria control, Indoor Residual Spraying (IRS) using insecticides (mostly Rambo®) purchased from shops and cleaning around house surroundings were practiced by >50% of respondents. Conclusion: Despite respondent’s awareness of mosquitoes as vectors of malaria as well as the use of ITNs, IRS, and cleaning of home surroundings to reduce malaria vectors burden, the ITNs coverage rate is very weak and more sensitization is also required at Akanda in Gabon.